TRANSFORMASI RENCANA PELAKSANAAN (RPP) DALAM MEWUJUDKAN PEMBELAJARAN YANG EFEKTIF DAN BERMAKNA - Nadiatus Sarifah; Sasi Aprilia; Fatma Yutistia Fara; Ma’mun Hanif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Lesson Plan (RPP) is often perceived merely as an administrative document that teachers are required to complete, resulting in its primary function as a learning guide not being utilized optimally. At the same time, technological advancements, changes in students' characteristics, and the demands of 21st-century skills require a transformation in instructional planning. This study aims to analyze the transformation of Lesson Plans (RPP) in realizing effective and meaningful learning. The study employed a qualitative approach using a library research method. Data were collected from various sources, including books, scientific journals, research articles, and relevant educational policy documents, and were analyzed using content analysis techniques. The findings indicate that the transformation of RPP is not merely focused on simplifying administrative requirements but also encourages teachers to design student-centered, contextual, adaptive, and technology-based learning. Furthermore, RPP plays a significant role in enhancing learning effectiveness through the systematic planning of learning objectives, activities, methods, and assessments. The implementation of RPP that is tailored to students’ needs can also create more meaningful learning experiences, increase student engagement, and support the development of 21st-century skills. Therefore, the transformation of RPP represents a strategic step toward improving the quality of learning and addressing the challenges of contemporary education.